2015
DOI: 10.1097/ajp.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective 2-Year Examination of Cognitive and Behavioral Correlates of Provoked Vestibulodynia Outcomes

Abstract: Background: Provoked vestibulodynia (PVD) is a common genital pain disorder in women, which is associated with sexual dysfunction and lowered sexual satisfaction. A potentially applicable cognitive-behavioral model of chronic pain and disability is the fearavoidance model (FAM) of pain. The FAM posits that cognitive variables, such as pain catastrophizing, fear, and anxiety lead to avoidance of pain-provoking behaviors (intercourse), resulting in continued pain and disability. Although some of the FAM variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 36 publications
(55 reference statements)
2
20
0
Order By: Relevance
“…Higher levels of catastrophizing, fear of pain, and hypervigilance and lower levels of self-efficacy correlate with increased pain in women with PVD, while higher levels of anxiety and avoidance and lower levels of self-efficacy were associated with their increased sexual dysfunction [64]. Moreover, there is evidence of a prospective relationship between cognitive variables and PVD, where higher levels of pain catastrophizing and lower levels of self-efficacy were shown to predict worse treatment outcomes in a randomized trial evaluating cognitive-behavioral therapy (CBT) [65], and increases in pain self-efficacy over a 2-year period were associated with better pain, sexual function, and sexual satisfaction outcomes [66].…”
Section: Psychological Factorsmentioning
confidence: 94%
“…Higher levels of catastrophizing, fear of pain, and hypervigilance and lower levels of self-efficacy correlate with increased pain in women with PVD, while higher levels of anxiety and avoidance and lower levels of self-efficacy were associated with their increased sexual dysfunction [64]. Moreover, there is evidence of a prospective relationship between cognitive variables and PVD, where higher levels of pain catastrophizing and lower levels of self-efficacy were shown to predict worse treatment outcomes in a randomized trial evaluating cognitive-behavioral therapy (CBT) [65], and increases in pain self-efficacy over a 2-year period were associated with better pain, sexual function, and sexual satisfaction outcomes [66].…”
Section: Psychological Factorsmentioning
confidence: 94%
“…In other chronic pain populations, avoidance patterns have been strongly associated with higher pain intensity and lower overall function (Leeuw et al, 2007;Vlaeyen and Linton, 2012). Similarly, in women with vulvovaginal pain, avoidance behaviour, pain catastrophizing and cognitive aspects of avoidance are prevalent (Gordon et al, 2003;Desrochers et al, 2009;Davis et al, 2015) and associated with higher pain intensity, well in line with the fear-avoidance model of pain (Vlaeyen and Linton, 2000). To our knowledge, only one study (Desrochers et al, 2009) has investigated and confirmed a cross-sectional link between avoidance coping, in the form of cognitive fear-avoidance tendencies, and lower sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked how many times in the past month they had attempted to have sexual intercourse with vaginal penetration. The actual number of attempts, successful or not, was taken as the behavioral measure of avoidance, with a lower number of attempts being indicative of more avoidance [43].…”
Section: Main Outcome Measuresmentioning
confidence: 99%